Language Use: A Study of Commissive Acts by the Eleventh Grade Students of SMA Negeri 1 Kubutambahan - ., Kadek Vani Septiani; ., Prof. Dr. Dewa Komang Tantra,Dip.,App.; ., Luh Diah Surya Adnyani, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Kata Kunci : Commissive acts, grammatical error, diction error, sources of error This study aimed: 1) to identify the patterns of commisive acts, 2) to identify the speech styles used in terms of formal and informal in expressing commisisve acts, 3) to identify types of error based on grammar and diction and, 4) to analyze the sources of error as committed by the eleventh grade students in a language program class at SMA Negeri 1 Kubutambahan. This study was a qualitative research. The subjects of this study were the eleventh grade students in a language program of SMA Negeri 1 Kubutambahan. The instruments were data elicitation, field note, interview guide, and recorder. The methods of data analysis were data transcription, analysis and category. The results of this study showed that the students produced various categories of speech act nsmely to promise, to refuse, to swear, to threaten, to offer, to accept, to thank, to request, to give opinion, to congratulate. The commissive acts produced by the students were to promise with total percentage 73%, to refuse with total percentage 14%, to swear with total percentage 12% and to threaten with total percentage 1,4%. The speech styles used in terms of formality by the students were 62,3% of formal language and 38,3% of informal language. The errors committed by the students were 80.8% of the grammatical errors and 19,1% of the diction errors. There were two types of sources of errors committed by the students namely interlingual with the total percentage 19,7% and intralingual or developmental factors with the total percentage 80,2%. keyword : Commissive acts, grammatical error, diction error, sources of error